2020
DOI: 10.1016/j.jfluidstructs.2020.102987
|View full text |Cite
|
Sign up to set email alerts
|

The effective prediction of wave-in-deck loads

Abstract: The present paper concerns the extreme wave loads acting on an offshore structure; specifically the wave-in-deck loading component that arises when the height of an incident wave crest exceeds the elevation of the topside structure. In this case wave inundation occurs, the resulting loads on the topside structure represent a significant part of the total wave load. A new model for the effective prediction of this important loading component is presented. This is based upon the conservation of momentum, is form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In undertaking this process, a 50 th wave gauge, placed outside the plan area of the topside, remained in place to serve as an assurance of the repeatability of the incident wave conditions. Full verification of the wave generation and the repeatability of the measurements is provided in Masterton and Swan (2008), Latheef and Swan (2013) and Ma (2017).…”
Section: Wave Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…In undertaking this process, a 50 th wave gauge, placed outside the plan area of the topside, remained in place to serve as an assurance of the repeatability of the incident wave conditions. Full verification of the wave generation and the repeatability of the measurements is provided in Masterton and Swan (2008), Latheef and Swan (2013) and Ma (2017).…”
Section: Wave Measurementmentioning
confidence: 99%
“…This was checked using a static system calibration showing excellent agreement and linearity within the measurement range. Whilst the complete details of the system are provided in Ma (2017), the success of the design is clearly demonstrated in Table 1; the application of a load in any one dof having a negligible response in all other loading components.…”
Section: Load Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Wave-in-deck occurs when there is no deck clearance or air gap between the water level and the bottom steel of topside structure when it is hit by the waves [43,44]. To avoid wave-in-deck, all offshore platforms need to be adequately designed by providing an allowance for the air gap [31]. If the air gap is expected to reduce over time, the lowest deck may be designed at a higher elevation or the equipment seated on the deck need to be designed to cater for the wave-in-deck load.…”
Section: Wave-in-deck Load and Reserve Strength Ratiomentioning
confidence: 99%
“…Studies performed by [22,[27][28][29][30][31] concluded that the wave-in-deck load needed to be considered in the pushover analysis. This was due to the fact that a huge wave hitting the offshore platform led to a high wave-in-deck load that could eventually resulted in significant platform damage and collapse.…”
Section: Introductionmentioning
confidence: 99%